Efektivitas Pengelolaan dan Pemanfaatan Taman Tematik di Kota Sukabumi - Marsela, Adinda Raya; Sampurna, Rizki Hegia; Meigawati, Dine (Jayapangus Press, 2025)
The growth of population and infrastructure development in urban areas, including Sukabumi City, has increased the urgency of providing green open spaces (GOS) as a crucial element in maintaining ecological balance and improving the quality of life for residents. The Sukabumi City Government has established thematic parks as part of public GOS to fulfill social, recreational, and aesthetic needs. However, the effectiveness of their management and utilization still faces several challenges. This study aims to analyze the effectiveness of the management and utilization of thematic parks in Sukabumi City using the effectiveness theory of (Nakamura and Smallwood, 1980), which includes five dimensions: goal achievement, efficiency, target group satisfaction, client responsiveness, and maintenance systems. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. Informants consisted of representatives from the Public Works and Spatial Planning Office (DPUTR) and local park users. The results indicate that the management of thematic parks in Sukabumi City is not yet fully effective. Several parks are not being utilized in accordance with their designated themes, and even misuse occurs, such as immoral activities and alcohol consumption, reflecting weak supervision. In terms of efficiency, budget constraints are the main obstacle to proper maintenance and facility provision. Although some parks are used quite well, overall public satisfaction remains suboptimal. In conclusion, the management and utilization of thematic parks in Sukabumi City have not been entirely effective. Improved coordination, supervision, public education, and adequate budget allocation are needed to ensure that the parks function according to their intended purposes.